Cryptogenic Organizing Pneumonia With Lung Nodules Secondary to Pulmonary Manifestation of Crohn Disease. Issue 10 (18th May 2017) - Zaman, Taufiq; Watson, Joseph; Zaman, Mohammad
Crohn disease is an immune-mediated inflammatory condition with gastrointestinal and extraintestinal manifestations in patients. Pulmonary involvement of Crohn disease is one manifestation. There have been case reports which have shown Crohn disease and lung nodules which were noted to be histopathological as cryptogenic organizing pneumonia (COP). In our case, a 22-year-old woman with Crohn disease was seen with complaints of chest pain and cough. Computed tomographic scan of chest showed multiple bilateral lung nodules, for which biopsy was done, which showed COP. The case study is followed by a deeper discussion of COP and the extraintestinal manifestation seen in inflammatory bowel disease.